Population Health, Infrastructure Development and FDI Inflows to Africa: A Regional Comparative Analysis - Aladejare , Samson Adeniyi (Asian Journal of Economic Modelling, 2022)
This study examined the effect of population health and infrastructure development on FDI inflows to Africa. Furthermore, a comparative study on the three biggest African regions, the ECOWAS, COMESA, and SADC regions, was conducted. A panel DOLS approach was adopted for 40 countries drawn from the regions from 1980 to 2017. Unlike empirical population health studies, the multidimensional effects of population health on FDI inflows were examined. The empirical findings from the study showed that population health significantly impacted FDI inflows to Africa, with strong effects in the ECOWAS, and weak effects in the COMESA and SADC regions. However, infrastructure development was found to be a major determinant of FDI flows to Africa and the three regions, thus suggesting that while foreign investors consider infrastructure development for investment in the three regions, population health is further considered on an aggregate level and by ECOWAS foreign investors.